Risk factors for Kaposi's sarcoma in HIV-positive subjects in Uganda. - Ziegler, J; Newton, R; Katongole-Mbidde, E; Mbulataiye, S; De Cock, K; Wabinga, H; Mugerwa, J; Katabira, E; Jaffe, H; Parkin, D; Reeves, G; Weiss, R; et al. (1997)
BACKGROUND: Kaposi's sarcoma (KS) is associated epidemiologically with HIV infection and with human herpesvirus 8 (HHV-8 or KSHV). Both KS and HIV infection are common in Uganda. We conducted a case-control study of 458 HIV-seropositive. Ugandan adults with KS and 568 HIV-seropositive subjects without KS to examine risk factors for HIV-associated KS. METHODS: We recruited newly diagnosed adult KS cases from five hospitals in Kampala, Uganda and controls from a large referral clinic for HIV infection at Mulago Hospital. All cases and controls were counselled and tested for HIV and answered an interviewer-administered questionnaire about their home, socio-economic conditions, lifestyle and sexual behaviour before they became ill. Only HIV-seropositive subjects were included in the analysis. RESULTS: There were 295 males and 163 females with KS and 227 male and 341 female controls. Age distribution was similar but there was a higher proportion of cases (45%) than controls (29%) residing in rural regions of Uganda. KS cases were more likely than controls to have a higher level of education (X2 for trend, 4.8; P = 0.03), to have occupations associated with affluence [chi 2 for heterogeneity, 17.3 on 5 degrees of freedom (df); P = 0.004] and to come from larger settlements [adjusted odds ratio (OR) for settlements of > 1000 versus 10-99 houses, 1.8; 95% confidence interval (CI), 1.1-3.0]. Cases were more likely than controls to have high household income (chi 2 for trend, 32.6; P < 0.001) and other markers of urban or rural wealth such as owning several cows (chi 2 for trend, 9.5; P = 0.002). Cases were more likely to travel away from home (adjusted OR, 1.6; 95% CI, 1.1-2.3) and more likely to have spent increasing time in contact with water (chi 2 for trend, 12.3; P < 0.001). Few indices of sexual behaviour were related to risk of KS, including reported number of sexual partners. Cases were more likely than controls to be married to one rather than several spouses (adjusted OR, 1.6; 95% CI, 1.2-2.2) and to have reported a history of sexually transmitted diseases (STD) (adjusted OR, 1.6; 95% CI, 1.2-2.3). CONCLUSIONS: Among HIV-infected subjects, KS cases are characterized by better education and greater affluence, compared with controls. Urban address, travel away from home, exposure to water, monogamous marriage and self-reported STD were also more frequent among KS cases than controls. The higher socio-economic status of persons with HIV and KS may be a marker for enhanced exposure to a possibly sexually transmitted agent, or for a delayed exposure to a childhood infection. The risk posed by exposure to water among KS cases requires further study.